2016
DOI: 10.1016/j.jhydrol.2016.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate vulnerability projections from Bayesian inference of multiple groundwater age tracers

Abstract: s u m m a r yNitrate is a major source of contamination of groundwater in the United States and around the world. We tested the applicability of multiple groundwater age tracers ( 3 H, 3 He, 4 He, 14 C, 13 C, and 85 Kr) in projecting future trends of nitrate concentration in 9 long-screened, public drinking water wells in Turlock, California, where nitrate concentrations are increasing toward the regulatory limit. Very low 85 Kr concentrations and apparent 3 H/ 3 He ages point to a relatively old modern fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 82 publications
(86 reference statements)
0
32
0
Order By: Relevance
“…Each domestic well water sample represents a mix of water age (Horn and Harter, 2009;Alikhani et al, 2016;Eberts et al, 2012). Ransom et al (2017) showed that land-use and nitrogen leaching patterns from the 1970s are most closely associated with recent groundwater nitrate measurements.…”
Section: Cvrwqcb Ranchomentioning
confidence: 99%
“…Each domestic well water sample represents a mix of water age (Horn and Harter, 2009;Alikhani et al, 2016;Eberts et al, 2012). Ransom et al (2017) showed that land-use and nitrogen leaching patterns from the 1970s are most closely associated with recent groundwater nitrate measurements.…”
Section: Cvrwqcb Ranchomentioning
confidence: 99%
“…Following the method presented in [24], to show the level of uncertainty associated with the kinetic model of the thermal isomerization of α-pinene, a Monte As it is seen in Figure 4, the duplicate experimental points are used in the parameter estimation without taking their average to take into consideration the real measurement errors. In this way, the experimental data provide better information about the parameter values.…”
Section: Resultsmentioning
confidence: 99%
“…Albrecht [29] Parameter estimation and uncertainty analysis by using Bayesian approach are widely used in different fields of science. Alikhani et al [30] applied Bayesian inference to estimate the confidence interval of groundwater residence time distributions by using multiple groundwater age tracers as observed data points.…”
Section: S S H Boosari Et Almentioning
confidence: 99%
“…Nonetheless, the information about the parameter values in other studies can be used to construct the prior distributions; and Bayesian approach can extract the information in the observed data set to enhance our confidence about the parameter values [31]. To obtain the posterior distribution by using the Bayesian approach, the mechanistic model needs to be solved by using Markov Chain techniques in a random walk approach [30]. Metropolis-Hasting algorithm is applied in this study to sample parameter sets of λ from posterior distribution ( )…”
Section: Bayesian Parameter Estimationmentioning
confidence: 99%